Prinsip dan Landasan Penggunaan Media Pembelajaran di Sekolah - Ananda Bunga Mutiara Dani Nasution; Ghina Agniya Suhulah; Putra Raihan Nur Alam; Usep Setiawan (JURNAL EDUKASI NONFORMAL, 2022)
In learning media activities have a crucial role in it. Various kinds of learning media are currently available and can be used according to learning needs. The role of the media in the learning process, among others, is that learning media must be able to act as a sense of intermediary or channel of good material so that students or students can get and know the learning material being studied using certain learning media. Therefore, the suitability between the learning media chosen and the learning material to be delivered can be one of the main keys to the success of the learning being carried out. The choice of learning media certainly cannot be arbitrary in determining, it would be very good if it followed exclusive principles in selecting learning media. . because if educators produce arbitrary media, they are worried that the teaching and learning activities will not go well and the material will not be fully conveyed to students. The principles of selecting instructional media refer to the considerations of a teacher in selecting and using instructional media for use or use in teaching and learning activities. Therefore, in the following, we will discuss the principles of using instructional media, both in lay and psychological terms. so that educators know and can choose the right media to help support the success of teaching and learning activities in the classroom. And will also be conveyed regarding the basis for the use of learning media.